Implementasi Data Mining Menggunakan Algoritma Fp-Growth Untuk Menganalisa Transaksi Penjualan Ekspor Online - Muhammad Hafizh; Triana Novita; Dodi Guswandi; Hadi Syahputra; Liga Mayola (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
In today's online technology, we have to learn various things so that we can adjust to social behavior, for example, buying and selling activities that cover all walks of life, now everyone doesn't hesitate to shop online. The online market is growing fast, especially in Indonesia. Anyone can sell and buy goods easily through online stores, so that people's purchasing power and sales increase due to the proliferation of online stores, XYZ stores are still beginners in terms of sales strategies so they try all efforts without careful preparation, one of the ways to do this is to expand its market coverage even to export goods abroad. the process of exporting goods in the current era is not a difficult thing to do, but it requires knowledge and preparation of a good strategy. from existing sales data can be analyzed to determine the right strategy in marketing goods. Data Mining is a science that helps analyze large amounts of data with the aim of gaining new knowledge that can be utilized. In Data Mining Analysis there is the FP-Growth algorithm which is a data mining technique for finding association rules from lots of data. This is known as the Association rule, where the rule will be determined from the minimum support and confidence results. the rules that are formed produce 10 rules out of 51 existing data, these rules help determine the export sales strategy at the XYZ store.